Uptake of the COVID-19 vaccine and its association with vaccine information and misinformation in Malawi - John Songo; Hannah S. Whitehead; Khumbo Phiri; Pericles Kalande; Eric Lungu; Sam Phiri; Joep van Oosterhout; Agnes Moses; Risa M. Hoffman; Corrina Moucheraud (Communications Medicine)
Abstract Background The information environment may be an important determinant of vaccination and other health behaviors including in low-income countries. Methods We administered a survey to 895 Malawian adults, asking about people’s COVID-19 vaccination history and their exposure to information (information sources and tone of this information) and misinformation (exposure to and belief in conspiracy theories) about the COVID-19 vaccine. Results Just under half (43%) of respondents had received at least one dose of the COVID-19 vaccine. Respondents heard about the COVID-19 vaccine from a median of 7 sources, most commonly from friends and neighbors, health care workers, and radio (each reported by >90%). Social media are the least positively- or neutrally-framed sources of information; and traditional medicine practitioners are the most common negatively-framed source of information. There is less information access among women, rural residents, and people with lower educational attainment. Many people hear conspiracy theories but say that they do not believe them. Hearing more COVID-19 vaccine information is positively associated with COVID-19 vaccination (aOR 1.09, 95% CI [1.03–1.15]), while believing COVID-19 vaccine misinformation is negatively associated (aOR 0.78, 95% CI [0.68–0.89]). Conclusions Vaccination programs should communicate through multiple information sources and find ways to reach groups with less information exposure.